Interferon-γ aptamers for the diagnosis of extra-pulmonary tuberculosis - Fanampe, Boitumelo Louisa (Department of Medicine, 2016)
Tuberculosis (TB) is a major global health problem. About 15-20% of the global population who are HIV negative have extra-pulmonary TB (EPTB) such as pleural TB. This increases to 50-70% in HIV positive people. The diagnosis of EPTB is challenging because of the low bacillary burden. Interferon gamma (IFN-γ) has been identified as a promising biomarker for the diagnosis of EPTB. The development of rapid and accurate point-of-care (POC) diagnostic technologies becomes crucial in controlling EPTB. Aptamers referred to as "synthetic antibodies" have been recently explored as a replacement for antibodies in diagnostic platforms. These single-stranded nucleic acid molecules have high affinity and specificity comparable, and in some instances even superior, to those of antibodies; in addition to their relatively low cost and simple method of production they have the potential to reduce assay turnaround time. The aim of this thesis was to develop aptamers to IFN-γ, a biomarker specific for EPTB, thus facilitating the development of aptamer-based POC tests for the diagnosis of EPTB.